Diagnosis of Lupus Nephritis – A Short Review - Alfredo Gutiérrez-Govea; María del Rosario Moreno-De-Los-Ríos; Miguel Medina-Pérez; Benjamín Gómez-Navarro; Dalia Celic Villalobos-Salazar (Journal of Medical Biomedical and Applied Sciences, 2021)
40-70% of patients withsystemic lupus erythematous suffer lupus nephritis, knowing how to detect early clinical manifestations, biomarkers and the importance of kidney biopsy are essentials to offer an adequate treatment and improve prognosis.